The fish pearl and other stories - Enriquez, Antonio (University of Santo Tomas Publishing House, 2016)
"Set in Zamboanga at the height of World War II. This novel casts a different light on the horrors of war by transplanting a colorful cast of characters -- men, women and children, civilians, politicians and soldiers, Filipinos, indigenous people and Japanese -- from common scenes of razed villages, bloody trenches, and blitzkrieg skies to a vast and unknown forest, in which they face the dangers of the jungle, Japanese atrocities, U.S. air raids, starvation and cannibalism, and strange half-human, half animal creatures: the river people and the cliff-dwellers. Toeing the line between morality and monstrosity, savagery and survival, they learn what it means to love and to forgive -- and ultimately, to be human -- in dark and trying times" -- [Publisher's website]